Kinetic and mechanistic insight into Lewis base and acid-mediated phenylselenoetherification of 2,6-dimethyl-hept-5-en-2-ol - Puchta, Ralph; Divac, Vera M.; Bugarčić, Zorica M.; et al. (Structural Chemistry, 2015)
Abstract Mechanistic and kinetic aspects, as well as quantum chemical calculations, for the formation of a tetrahydrofurane ring by cyclization of the highly substituted alcohol-2,6-dimethyl-hept-5-en-2-ol with phenylselenohalides (PhSeCl and PhSeBr), in the presence of various Lewis bases (piperidine, triethylamine, pyridine and quinoline) and Lewis acids (CoCl2, SnCl2) as additives were studied. The substituted tetrahydrofuran ring is common motif in many natural products, especially in bioactive marine macrolides. Due to the presence of additives in reactions, the high regioselectivity was achieved, and the tetrahydrofuran type of ether in all studied reactions was obtained in excess in regard to the six-membered cyclic ether. In addition, kinetic aspects of reactions mediated by Lewis bases were studied by UV-Vis spectroscopy (in THF, at 288 K), as reactions of pseudo-first-order. Obtained values for rate constants proved catalytic role of additives and indicated that the reaction rate depends on pKa values of used base as well as on their ability for formation of hydrogen bond with OH-alcohols group.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Cyclization; Kinetics; Quantum calculations; Transition state structure